Design of non-equal-strut stent hoops for structural optimization of thoracic aortic stent-grafts. - Yan, Shiju; Song, Chengli; Si, Yi; Zhao, Yiwen (Minimally Invasive Therapy & Allied Technologies, 2022)
Endovascular aortic aneurysm repair (EVAR) with stent-grafts is used widely for the treatment of thoracic aortic aneurysms (TAA). Inappropriate design of stent-grafts may lead to complications such as endoleak, stent-graft migration and new entries, causes of which may be inappropriate radial support force or insufficient longitudinal flexibility of the stent-grafts. To improve the mechanical performance of the stent-grafts, a type of non-equal-strut stent hoops was proposed, and the influence of structural parameters on the mechanical performance was studied. Results of numerical simulation and physical experiments show that by using the proposed non-equal-strut stent hoops, radial support force and longitudinal flexibility of stent-grafts can be reconciled and balanced. Results of this study could be used to facilitate radial force control and longitudinal flexibility enhancement in the design of aortic stent-grafts.